Upstage Rate of Complex Sclerosing Lesions/Radial Scars. Issue 5 (May 2022) - Jones, Veronica M.; Pearce, Jane B.; Khalil, Maryam; Cain, Olivia; Coldren, Daniel; Martin, Harrison; Howard-McNatt, Marissa; Levine, Edward; Chiba, Akiko
Background: Radial scars (RS) and complex sclerosing lesions (CSL) are breast radiologic findings described as small, stellate lesions causing architectural distortion. This can mimic malignancy. Core needle biopsy (CNB) is often performed. Advances in breast imaging have led to increased detection of RS/CSL. The upstage rate of RS/CSL to in situ or invasive disease is 0-40%. We sought to determine the upstaging rate of RS/CSL to in situ, invasive disease, or high-risk lesion at our institution to create excision guidelines. Methods: The pathology database of a single center was searched for RS/CSL, from January 2013 to September 2020. We included CNB without malignancy or high-risk lesion (eg, atypical ductal hyperplasia). Patient demographics, indications for biopsy, imaging findings, biopsy procedure, and final pathology were collected. Results: Forty-four patients were included. 52.3% had CNB for architectural distortion on mammography, 18.2% for mass, 11.4% for calcifications, 2.3% for abnormal MRI, and 15.9% for multiple reasons (eg, calcifications and mass). Most had an ultrasound: 43.2% had no abnormality and 34.1% had a mass. All CNB were vacuum assisted, 65.9% with 9-gauge needle, and averaged 10.0 cores. 77.3% were stereotactic biopsies, 13.6% ultrasound, and 6.8% MRI. 59.1% had excision after CNB. 82.1% of patients did not upstage. One patient upstaged to invasive ductal carcinoma (3.6%) and two patients to high-risk lesion (7.1%). Discussion: There was low upstage rate of RS/CSL on excisional biopsy. Centers could consider close surveillance for RS/CSL on CNB. Longer follow-up in cases of deferred excision is needed to ensure oncologic safety.